Alphaworld: ice and snow - Wang, Lee (Oxford University Press Melbourne, 2004)
Ice and snow transform the landscape into a winter wonderland, blanketing everything in glistening white. The air turns crisp and cold, and the sound of crunching snow underfoot fills the silence. Ice forms delicate patterns on windows and glistens on branches, creating a magical atmosphere. Children bundle up to build snowmen, engage in snowball fights, and glide across frozen ponds. The beauty of frost-kissed mornings and the quiet stillness of snow-covered nights invite a sense of peace and wonder. Yet, beneath the enchantment, ice and snow can also bring challenges, requiring caution and care in navigating their slippery surfaces. Overall, they evoke a unique blend of joy and awe, reminding us of nature's artistry.